Hybrid Busy tone and Carrier sense-based MAC protocol in multi-hop ad hoc networks. (18th June 2007) - Yang, Daiqin; Shao, Wenjian; Shen, Dongxu; Li, Victor O.K.
In multi-hop ad hoc networks, receiver busy tone-based Media Access Control (MAC) protocols have been proposed to solve both the hidden terminal problem and the exposed terminal problem of carrier sense-based MAC protocols. However, with only busy tone signals, senders cannot determine the receiving status of their intended receivers. Invitations from intended senders may fail owing to the non-receivable status of their intended receivers rather than owing to collisions. In this paper, we propose a novel Hybrid Busy tone and Carrier sense-based MAC protocol (HBCMA). Simulation results show that HBCMA achieves better performance than a purely busy tone-based protocol.